2010
DOI: 10.1080/10550887.2010.531672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methadone Maintenance Treatment on Heroin Craving, a Literature Review

Abstract: Despite agreement that methadone maintenance treatment (MMT) is an effective and safe option for treatment of heroin dependence, there have been controversies about its effect on heroin craving. A systematic literature review of the PubMed database was used to find studies eligible for inclusion in the study. The authors present the results of 16 articles that met all inclusion criteria. Overall, 7 studies reported that methadone could reduce heroin craving, 4 studies reported that patients in MMT are still at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 56 publications
1
53
0
1
Order By: Relevance
“…Solid evidence has consistently indicated that MMT is an effective treatment for opiate dependence (Fareed et al, 2011;Farrell et al, 1994;Garrido & Troconiz, 1999;Joseph, Stancliff, & Langrod, 2000), and longer retention time has been consistently associated with better outcomes (Flynn, Joe, Broome, Simpson, & Brown, 2003;Gossop, Marsden, Stewart, Lehmann, & Strang, 1999;Hubbard, Craddock, & Anderson, 2003;Joe, Simpson, & Broome, 1999). That is, retention is a critical issue, because dropping out from MMT can lead to relapse and further adverse consequences (Gerstein, 1994;Pettinati et al, 2008;Rabinowitz & Marjefsky, 1998;Simpson, Joe, & Rowan-Szal, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Solid evidence has consistently indicated that MMT is an effective treatment for opiate dependence (Fareed et al, 2011;Farrell et al, 1994;Garrido & Troconiz, 1999;Joseph, Stancliff, & Langrod, 2000), and longer retention time has been consistently associated with better outcomes (Flynn, Joe, Broome, Simpson, & Brown, 2003;Gossop, Marsden, Stewart, Lehmann, & Strang, 1999;Hubbard, Craddock, & Anderson, 2003;Joe, Simpson, & Broome, 1999). That is, retention is a critical issue, because dropping out from MMT can lead to relapse and further adverse consequences (Gerstein, 1994;Pettinati et al, 2008;Rabinowitz & Marjefsky, 1998;Simpson, Joe, & Rowan-Szal, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[12]. According to a systematic literature review of Pubmed articles, seven studies reported that methadone reduced heroin cravings, while four suggested that patients in MMT were still susceptible to heroin cravings [36]. It is possible that for some patients, methadone does not reduce heroin cravings, leading to relapse into heroin addiction.…”
Section: Reasons For Breaks and Staying In Mmtmentioning
confidence: 99%
“…Treatment options have been developed for heroin addiction, but fewer options have been studied for abuse of OXY or other prescription opioids. Agonist therapies for heroin addiction such as methadone and buprenorphine can be very effective, but their own abuse potential and risk of side effects obligate careful and frequent monitoring, and their therapeutic use is legally restricted to those regularly using substantial quantities of opioid over a sustained period of time (Fareed et al, 2011). Many prescription opioid abusers do not fit this profile because their opioid use is oral rather than intravenous and may be sporadic, yet they still run the risk of overdose, social disruption, and transition to intravenous drug use and addiction.…”
Section: Introductionmentioning
confidence: 99%